Contemporary Philosophy and the Latter-day Saint Tradition (Taylor & Francis, 2026)
The Latter-day Saint theological tradition includes philosophically interesting commitments that are distinctive in relation to Classical Christian traditions. This is the first volume to offer an explicitly philosophical treatment of key ideas in the Latter-day Saint tradition. Contemporary philosophy of religion has paid little attention to minority and heterodox traditions like that of the Latter-day Saints. This volume provides a starting place for the inclusion of the Latter-day Saint tradition in philosophy of religion. It collects original essays from contemporary philosophers, most of whom come from Latter-day Saint backgrounds and tackle philosophical issues concerning the Latter-day Saint tradition from an internal perspective. The chapters explore the existence and nature of God, ethics and morality, and various issues related to the Church of Jesus Christ of Latter-day Saints. Contemporary Philosophy and the Latter-day Saint Tradition will appeal to researchers and graduate students working in philosophy of religion, Mormon studies, and theology.